the prince and the pauper : philippine edition - Twain, Mark; Mark Twain (First philippine reprint Cengage learning, 2010)
Mark Twain$1 (Bs The Prince and the Pauper is a 16th-century tale of mistaken identity where Prince Edward Tudor and poor Tom Canty swap clothes and lives. They navigate opposite worlds, experiencing harsh survival and royal duty, teaching them compassion and justice, ultimately leading to a more empathetic, just kingdom when Edward resumes his throne. s
English